Factors Affecting the Sustainability Reporting of IDX Companies - Nurul Qomariah (Profesional Muda Cendekia Publishing, 2021)
The purposeof the study to determine the effect of Profitability, Leverage, AuditorType, Institutional Ownership, CSR Committees, Industries Close to Consumers,Environmentally Sensitive Industries, and Employee Oriented Industries onSustainability Reporting Reports on Companies Listed on the IDX in 2016-2018.The population in this study were all companies listed on the IDX in 2016-2018with a total of 518 companies. The sampling technique used was purposivesampling technique and the research sample obtained was 38 companies. Thistype of research is quantitative research. The data analysis technique used is touse multiple regression analysis techniques with data management using theSPSS version 16 program.The results showed that Profitability had a negative effect on SustainabilityReporting, Leverage had no effect on Sustainability Reporting, Auditor Type hadno effect on Sustainability Reporting, Institutional Ownership had no effect onSustainability Reporting, CSR Committee had no effect on SustainabilityReporting, Industries that were close to consumers had no effect on SustainabilityReporting. Sustainability Reporting, Industry that is Sensitive to theEnvironment has an effect on Sustainability Reporting, and Industry Orientedwith Employees has no effect on Sustainability Reporting.